The Post War Performance of the Lebanese Banks Using the Balanced Scorecard: A Case Study - Khatib, Anis EL (International Journal of Management and Sustainability, 2020)
This study covers a 15 years period after the end of the Lebanese civil war, that is from 1990 to 2004.The importance of the period under study comes from the many Lebanese banking industry’s internal and external environmental changes. This period witnessed mainly the stabilization of the foreign exchange rate, the financing of the reconstruction process, the heavy subscription of banks in Lebanese T-bills, the unprecedented mergers and acquisitions among Lebanese banks, and the expanding of banking activities abroad, and toward retailing and banc-assurance. A balanced Scorecard is constructed using the four perspectives as developed by Kaplan and Norton in 1992. Five measures have been developed for each of the four perspectives, and the case study approach is employed. The determination of the measures is based upon those used in previous works, and the specific conditions and constraints related to the banking industry in Lebanon. The study concludes that the highest performing perspective is the Customer, followed by the Learning and Growth, and the Internal Process. The study recommends that Lebanese authorities start encouraging banks to adopt Performance Management Systems (PMSs) to reflect both the financial and the non-financial activities of banks. This is crucial since the Lebanese Banking Sector is anticipated to face a new era of challenges due to the expected extraction of gas resources, the reconstruction of Syria, and the development of the banking system in the Arab Gulf Area.